2017
DOI: 10.1007/s11103-017-0601-0
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism underlying anthocyanin metabolism in apple using the MdMYB16 and MdbHLH33 genes

Abstract: MdMYB16 forms homodimers and directly inhibits anthocyanin synthesis via its C-terminal EAR repressor. It weakened the inhibitory effect of MdMYB16 on anthocyanin synthesis when overexpressing MdbHLH33 in callus overexpressing MdMYB16. MdMYB16 could interact with MdbHLH33. Anthocyanins are strong antioxidants that play a key role in the prevention of cardiovascular disease, cancer, and diabetes. The germplasm of Malus sieversii f. neidzwetzkyana is important for the study of anthocyanin metabolism. To date, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
127
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(129 citation statements)
references
References 56 publications
2
127
0
Order By: Relevance
“…In Arabidopsis, AtPAP1, AtPAP2, AtMYB113, AtMYB114, and AtMYBL2 act as crucial modulators of flavonoid biosynthesis (Borevitz et al, 2000;Gonzalez et al, 2008;Matsui et al, 2008;Rowan et al, 2009). In apple, MdMYB1/10/A, MdMYB3, MdMYB12, MdMYB16, and MdMYB22 positively affect flavonoid biosynthesis (Takos et al, 2006;Ban et al, 2007;Espley et al, 2007;Vimolmangkang et al, 2013;Xu et al, 2017;Wang et al, 2017). Decreased ROS accumulation in MdMYB23-overexpressing apple calli and Arabidopsis in response to cold stress suggested that MdMYB23 might be involved in the modulation of flavonoid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, AtPAP1, AtPAP2, AtMYB113, AtMYB114, and AtMYBL2 act as crucial modulators of flavonoid biosynthesis (Borevitz et al, 2000;Gonzalez et al, 2008;Matsui et al, 2008;Rowan et al, 2009). In apple, MdMYB1/10/A, MdMYB3, MdMYB12, MdMYB16, and MdMYB22 positively affect flavonoid biosynthesis (Takos et al, 2006;Ban et al, 2007;Espley et al, 2007;Vimolmangkang et al, 2013;Xu et al, 2017;Wang et al, 2017). Decreased ROS accumulation in MdMYB23-overexpressing apple calli and Arabidopsis in response to cold stress suggested that MdMYB23 might be involved in the modulation of flavonoid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, apple (Malus × domestica) MYB16 directly binds MdANS and MdUFGT, and inhibits their expression through the C-terminal EAR motif. AtMYB3 inhibits the biosynthesis of sinapoyl malate and anthocyanin directly by targeting and repressing AtC4H [29,41,42].…”
Section: Mechanisms Of Subgroup 4 R2r3 Myb Repressors In Anthocyanin mentioning
confidence: 99%
“…The expression of UFGT has been inhibited in anthocyanin MYB repressor-overexpression lines. However, only a few MYB repressors, apple MdMYB16 and peach PpMYB18, for instance, can target the promoter of UFGT or inhibit the promoter activity of UFGT directly [30,41,42]. The actions of lignin and flavonol MYB regulators usually do not require the bHLH cofactor, while the actions of anthocyanin and proanthocyanidin MYB regulators generally do require the bHLH cofactor [30].…”
Section: Mechanisms Of Subgroup 4 R2r3 Myb Repressors In Anthocyanin mentioning
confidence: 99%
“…Over the past decade, our group has constructed a series of hybrid populations of M. sieversii f. niedzwetzkyana (Luntai National Fruit Germplasm Resources Garden, China) crossed with two excellent white‐fleshed varieties (Fuji & Gala). So far, these studies have focused mainly on their genetic structure (Zhang, Chen, He, Liu, & Tao, ), tissue cryopreservation in vitro (Wu et al., ), breeding of functional apples (Chen et al., ), the mechanism of anthocyanin and flavonoid formation (Wang et al., ; Wang et al., ; Xu et al., ), and processing technology (Zuo et al., ). However, the phytochemical characteristics of new red‐fleshed varieties in China, such as free phenolics, bound phenolics, antioxidant activity especially in cellular antioxidant activity (CAA) and antiproliferative activity, have not been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%